Exploring The Impact Of Auditor Independence, Dysfunctional Behavior And Professional Skepticism On Audit Quality - Kelvin; Handra Tipa (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to examine the effect of auditor independence, dysfunctional auditor behavior, and professional skepticism on audit quality. Using a quantitative approach, the research adopts a positivist paradigm that assumes behavioral constructs can be objectively measured and statistically analyzed to determine causal relationships. The study was conducted in Batam, Indonesia, with auditors working in public accounting firms registered in the 2025 IAPI directory. The total population consisted of 14 public accounting firms, and the sampling technique used was census sampling (saturated sampling), which included all eligible auditors to ensure a comprehensive representation of audit practices in the region. Primary data were collected through structured questionnaires distributed via Google Forms using a five-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). Data analysis SPSS due to its suitability for handling complex relationships among latent variables with relatively small to medium sample sizes. The results based on Table 2 show that the independence variable has a t-value of 2.269 > t-table 1.98498 with a significance level of 0.000 < 0.05, indicating that independence significantly affects audit quality. The dysfunctional auditor behavior variable shows a t-value of 2.657 > 1.98498 and a significance of 0.000 < 0.05, meaning it significantly influences audit quality. Similarly, professional skepticism has a t-value of 2.997 > 1.98498 and a significance of 0.000 < 0.05, confirming its significant impact on audit quality. Overall, the findings highlight that independence, auditor behavior, and professional skepticism are key determinants of audit quality in public accounting firms in Batam.